A series of organic–inorganic hybrid materials consisting of flexible organic amine modified polyoxomolybdates: synthesis, structures and properties. Issue 108 (8th November 2016) - Gong, Chunhua; Zeng, Xianghua; Zhu, Chengfeng; Shu, Jiahui; Xiao, Pingxiu; Xu, Hao; Liu, Lichun; Zhang, Junyong; Zeng, Qingdao; Xie, Jingli
Abstract : A series of hybrid materials consisting of Tris[(2-pyridyl)methyl]amine modified polyoxomolybdates were obtained and some complexes have efficient photocatalytic activities to degrade pararosaniline hydrochloride dye molecules. Abstract : A series of organic–inorganic hybrid complexes based on different types of polyoxomolybdates and transition metal complexes, namely, [Zn2 (TPMA)2 (H2 P2 Mo5 O23 )]·11H2 O (1 ), [Zn2 (TPMA)2 (Mo8 O26 )] (2 ), [Co2 (TPMA)2 (Mo8 O26 )] (3 ), [Ni2 (TPMA)2 (Mo8 O26 )(H2 O)2 ] (4 ), [Ni2 (TPMA)2 (2-PA)(H2 O)](PMo12 O40 ) (5 ) [Cu2 (TPMA)2 (Mo8 O26 )] (6 ), 2[Cu(TPMA)(CrMo6 (OH)6 O18 )]·H[Cu2 (TPMA)2 (CrMo6 (OH)6 O18 )]·4H2 O (7 ) (TPMA = Tris[(2-pyridyl)methyl]amine, 2-PA = 2-picolinic acid), have been successfully synthesized under hydrothermal conditions. All complexes were characterized by single-crystal X-ray structural analysis, powder X-ray diffraction, IR spectroscopy and TG analysis. All the complexes showed polyoxomolybdate-based zero-dimensional (0D) structures, and could be further extended into three-dimensional (3D) supramolecular frameworks through hydrogen bonding interactions. In addition, the electrochemical properties of complexes1–7 have been investigated. Interestingly, some complexes have efficient photocatalytic activities to degradate pararosaniline hydrochloride dye molecules.